INVESTIGATING THE EFFECT OF NANO-METALS ON POULTRY HISTOLOGY: A REVIEW - Hashim Hadi Al-Jebory , Mohammed Khalil Ibrahim Al-Saeedi, Rasha Fajer Al-Jebory, Hala Faez Abdul-Hadi Al-Jewahery, Majeed Ajafar, I. M. A. Abd ALzahra, Mohammad A. Elsagheer, Mohamed R. Eletmany (Chelonian Research Foundation, 2024)
Nanotechnology is a double-edged technology, given the benefits and uses of nano-metals that are common and many in the poultry industry, using them as antibacterials, antioxidants, and antifungals, and in improving immunity and fertility, as well as adding nano-mineral elements in feed and technology for transporting medicines and vaccines, however, many nano-metals may hurt the body cell and various body tissues (especially the liver, kidneys, and testicles), as high concentrations of it may cause necrosis and damage to the cells of the liver, kidneys, and testicles, which may harm the bird’s health and thus its productivity, in addition, there may be a cumulative effect of the nano-metal in some tissues, which may be transmitted to the consumer, causing health damage, which may violate global health controls and conditions, and this is what called for nano green synthesis technology and organic chickens.